HUTS a feasibility study on a Hybrid Urban Transit System - Diaz, Renz Patrick L.; Españo, Julius Rene C.; Kwan, Kevin Kenneth T.; Señires, Luis Gabriel D. (College of Engineering, 2013)
Transportation schemes in the Philippines are designed to have cheap fares at the compromise of quality. This is the concept behind mass transportation where the main goal is to service as many people as possible. Currently, a transportation system that aims to improve the standards of living in Metro Manila by guaranteeing quality, security and reliability, unfortunately, does not exist. Because of this, the idea of a Hybrid Urban Transit System was born. HUTS aims to combine the concepts of school buses, carpools and airplane services to create a deluxe shuttle service that aims to give first-class amenities to its clients to eliminate the unnecessary stress and fatigue brought about by travel while ensuring its reliability by always bringing passengers to their workplaces on time. The service would mainly cater to BPO executives. By studying and conducting interviews with relevant industries, a forecast for the supply and demand over a specific time frame was created, as illustrated in the following table: Initially, the service would be offered only to people located in the South of Metro Manila because of three major considerations: Historical traffic conditions, Predictability of traffic, Availability and effectiveness of alternate routes. HUTS, classified as a transportation service, is expected to be heavy on capital investment. As a result, the company would capitalize on the service's exclusivity to ensure that it remains marketable and profitable. Apart from the main transportation service that the business would offer, additional revenue streams include vehicle wrapping and putting spaces up for lease. Doing this would not only generate added income but also associate the brand with other types of products and services that offer the same high level of quality. Moreover, this would help in making the establishment of the business easier and more secure by reducing the necessary costs the company would otherwise incur. The table below shows a summary of the service's net profit over the relevant time period.